Application of Simulation Methods for Study on Availability of One-Aisle Machine Order Picking Process - Mariusz Kostrzewski; Jozef Gnap; Pavol Varjan; Marek Likos (Communications - Scientific letters of the University of Zilina, 2020)
The main aim of the paper is the analysis of simulation model reflecting selected in-warehouse logistics processes in the aspect of their availability. For this purpose, one-aisle machine picking problem with use of a stochastic random simulation is studied, with a special focus on reliability of the system to disturbances and maintenance scheduling. The methodology in the research consists of classic measures of reliability. The model is designed in order to analyze availability of selected parameters of randomly generated order picking process. One of key-results of the paper is answer for question if a mean time to failure can be treated as a value of time when the first failure in the system occurs. A summary of the contribution includes discussion and the perspectives for further research in the subject matter.